Characterization and vectorization of siRNA targeting RET/PTC1 in human papillary thyroid carcinoma cells - Massade, L. (Вiopolymers and Cell, 2011)
RET/PTC1 fusion oncogene is the most common genetic alteration identified to date in thyroid papillary carcinomas (PTC) and represents a good target forsmall interfering RNA (siRNA). Our aim was: i) to target the RET/PTC1 oncogene by siRNAs, ii) to assess the knockdown effects on cell growth and cell cycle regulation and iii) to vectorize it in order to protect it from degradation. Methods. Human cell lines expressing RET/PTC1 were transfected by siRNA RET/PTC1, inhibition of the oncogene expression was assessed by qRT-PCR and by Western blot. Conjugation of siRNA RET/PTC1 to squalene was performed by coupling it to squalene. In vivo studies are performed in nude mice. Conclusion. In this short com- munication, we report the main published results obtained during last years. Keywords: RET/PTC1, siRNA, thyroid papillary carcinomas.